Changing Trends in Japanese Students Studying Abroad - Bradford, Annette (International Higher Education, 2015)
After a dramatic decline in the number of Japanese students studying abroad and significant media focus on the inward-looking tendencies of Japanese students, much attention in Japan has turned to outward mobility. This article discusses the number of students overseas, noting a recent uptick. It examines student perspectives toward studying abroad and comments on new policy initiatives.